A Review of Important Activities and Studies 1964-65 - Planning Commission (Planning Commission Government of India, 1965)
This consolidated summary reviews the major activities, studies, and policy initiatives undertaken by the Planning Commission of India between the mid-1960s and early 1970s. It highlights the formulation and implementation of the Fourth Five-Year Plan, the use of perspective planning, and the Commission’s responses to economic challenges such as food shortages, energy demands, and infrastructure constraints. Emphasis is placed on agriculture, industry, transport, power, education, health, and social welfare, supported by extensive research, evaluation, and inter-governmental coordination. The report underscores the role of empirical analysis, institutional reforms, and long-term strategic planning in shaping India’s developmental trajectory toward balanced growth and social equity.
Government of India Planning Commission
Keywords: Fourth Five-Year Plan; Perspective Planning; Agricultural Development; Industrial Growth; Infrastructure Development; Programme Evaluation; Socio-Economic Research; Energy Planning; Education and Health; Rural Development; Policy Coordination